Evaluation of finger cartilage composition in recreational climbers with 7 Tesla T2 mapping magnetic resonance imaging - Bayer, Thomas; Brockhoff, Marie-Jo; Nagel, Armin M.; Adler, Werner; Lutter, Christoph; Janka, Rolf; Heiss, Rafael; Uder, Michael; Roemer, Frank W. (Frontiers in Sports and Active Living, 2023)
Sport climbing may lead to tissue adaptation including finger cartilage before apparent surface damage is detectable. The main aim was to assess finger cartilage composition with T2 mapping in young, active climbers and to compare the results to a non-climbers' collective. A secondary aim was to compare whether differences in cartilage T2 times are observed between older vs. younger volunteers.7 Tesla MRI of the fingers Dig.2-4 was performed using a multi-echo spin echo sequence. Manual segmentation of 3 ROIs at the metacarpal heads, 1 ROI at the base phalanx and 1 ROI at the proximal interphalangeal joint was performed. Included were 13 volunteers without history of trauma who are regularly performing climbing activities as a recreational sport (> 20 hours/month). These were age-matched with 10 control subjects not performing climbing activities.Mean age was 32.4 years for the climbing group and 25.8 years for the controls. Mean T2 values for the 5 different ROIs were 42.2 +/-7.8 msec for climbers and 41.4 +/-6.8 msec for non-climbers. No significant differences were observed for T2 values between both groups. However, higher age had a significant impact on T2 values for all assessed ROIs (higher age 44.2 +/-9.5, younger age 32.9 +/-5.7, p = 0.001).This study evaluated the cartilage composition of young, engaged climbers with a T2 mapping MRI technique with the purpose to depict early onset joint changes. No negative impact on cartilage composition due to the sport activity was found, whereas age-related effects on the cartilage seemed to be more prominent.LEVEL OF EVIDENCE: IV.